Does Antiviral Therapy for Chronic Hepatitis B Reduce the Risk of Hepatocellular Carcinoma? - Abu-Amara, Mahmoud; Feld, Jordan J. (Seminars in Liver Disease, 2013)
Chronic hepatitis B infection (CHB) is common and can lead to serious consequences including liver cirrhosis, failure, and hepatocellular carcinoma (HCC). The hepatitis B virus (HBV) has a simple genome, but a complex lifecycle that includes the production of covalently closed circular DNA (cccDNA). Currently approved antiviral treatments for CHB include interferon (IFN) and nucleos(t)ide analogues. These drugs work either by stimulating the immune system to eliminate virus-infected cells or to inhibit viral replication, respectively. The drugs do not affect the cccDNA pool in the nucleus; therefore, this molecule represents a persistent source of recurrent infection that is difficult to eradicate. With longer-term follow-up of patients treated with antiviral therapy, investigators have looked at whether treatment can prevent the development of HCC. Unfortunately, the data are fairly heterogeneous in terms of both quality and conclusions. IFN appears to reduce the risk of HCC, but the benefit seems to be restricted to cirrhotic patients who have a lasting response to therapy. Oral agents successfully suppress HBV DNA replication and slow or even reverse hepatic fibrosis. Studies suggest that long-term therapy reduces the risk of HCC in patients with active disease and again primarily in those with advanced fibrosis or cirrhosis. The mechanism by which any of the therapies reduce the risk of HCC is not clear. The authors review the lifecycle of HBV and mechanisms by which the virus may be carcinogenic followed by a review of the literature on the efficacy of therapy in reducing the risk of HCC.
Keywords: chronic hepatitis B infection; hepatocellular carcinoma; antivirals; interferon; nucleos(t)ide analogues